Comorbidity of psychiatric and somatic disorders among patients diagnosed with depression - Kuśmierek, Maciej; Florkowski, Antoni; Gałecki, Piotr; Talarowska, Monika (Current Problems of Psychiatry, 2011)
Background: Depressive disorders are the most common mental disorders. As the symptom they are often accompanied by other diseases. The aim of the study was to determine the extent and nature of the coexistence of somatic disorders among patients treated for depressive disorders. Material and methods: One hundred and twenty medical records of patients aged 18-64 years with a diagnosis of depressive episode (F 32.0-32.9 F), DE or recurrent depressive disorder (F33.0-33.9 F), RDD, were used in the study. In the analysis using the survey research there were medical records, diagnostic tests and specialist consultations for the presence of somatic disorders. Results: The presence of somatic symptoms during psychiatric hospitalization was confirmed in 52.5% of subjects. This phenomenon affected approximately 39% of patients with DE and 61% of patients with RDD (p = 0.021). Sixty eight percent (68%) of respondents had at least one comorbid somatic illness (among 57% of patients with DE and 76% of patients with RDD). Higher incidence of physical illness in patients with RDD was statistically significant (p = 0.028). Conclusions: 1. More than 60% of patients hospitalized for major depressive disorder are diagnosed with concomitant physical illness. Over 50% of them present somatic symptoms. 2. Somatic symptoms and somatic diseases are frequently observed among patients with RDD, compared to patients with DE. 3. The most common somatic diseases in patients with depressive disorders are hypertension and diabetes.